Strategic Outsourcing in the Digital Age: Cyber Risk Management and Operational Performance in Malaysian BPOs - Fidhien, Ferdio Ghifary; Dodie Tricahyono; Edi Witjara (JAF (Journal of Accounting and Finance), 2025)
Business Process Outsourcing (BPO) companies have become vital players in Malaysia's post-pandemic digital economy, providing critical non-core services such as technology infrastructure management, customer support, and business process administration. However, the rapid growth of BPOs has also brought increased risks related to data security, fraud, and cyber threats, raising concerns about operational performance and good corporate governance. This study investigates the combined influence of outsourcing strategy, data security, fraud risk management, and cyber threats on the operational performance of Malaysian BPO firms listed on Bursa Malaysia during the 2021–2024 period and examines the implications for good governance. A quantitative explanatory approach was employed, utilizing SEM-PLS for hypothesis testing. The findings reveal that effective outsourcing strategies, robust data security frameworks, proactive fraud risk management, and mitigation of cyber threats significantly enhance operational performance. Furthermore, improved operational performance contributes positively to the implementation of good corporate governance principles. This research provides both theoretical and practical contributions: it enriches the literature on BPO governance and operational risk in the digital era and offers strategic insights for companies and regulators aiming to enhance accountability, transparency, and resilience in outsourcing operations. The study contributes to both governance literature and practical frameworks by integrating fraud deterrence, cybersecurity, and operational performance in the BPO sector.